PSnoD: identifying potential snoRNA-disease associations based on bounded nuclear norm regularization. Issue 4 (12th July 2022) - Sun, Zijie; Huang, Qinlai; Yang, Yuhe; Li, Shihao; Lv, Hao; Zhang, Yang; Lin, Hao; Ning, Lin
Abstract: Many studies have proved that small nucleolar RNAs (snoRNAs) play critical roles in the development of various human complex diseases. Discovering the associations between snoRNAs and diseases is an important step toward understanding the pathogenesis and characteristics of diseases. However, uncovering associations via traditional experimental approaches is costly and time-consuming. This study proposed a bounded nuclear norm regularization-based method, called PSnoD, to predict snoRNA-disease associations. Benchmark experiments showed that compared with the state-of-the-art methods, PSnoD achieved a superior performance in the 5-fold stratified shuffle split. PSnoD produced a robust performance with an area under receiver-operating characteristic of 0.90 and an area under precision-recall of 0.55, highlighting the effectiveness of our proposed method. In addition, the computational efficiency of PSnoD was also demonstrated by comparison with other matrix completion techniques. More importantly, the case study further elucidated the ability of PSnoD to screen potential snoRNA-disease associations. The code of PSnoD has been uploaded to https://github.com/linDing-groups/PSnoD . Based on PSnoD, we established a web server that is freely accessed via http://psnod.lin-group.cn/ .